Controllable Synthesis of Band-Gap-Tunable and Monolayer Transition-Metal Dichalcogenide Alloys - Su, Sheng-Han; Hsu, Wei-Ting; Hsu, Chang-Lung; Chen, Chang-Hsiao; Chiu, Ming-Hui; Lin, Yung-Chang; Chang, Wen-Hao; Suenaga, Kazu; He, Jr-Hau; Li, Lain-Jong (Frontiers in Energy Research, 2014)
The electronic and optical properties of transition metal dichalcogenide (TMD) materials are directly governed by their energy gap; thus, the band gap engineering has become an important topic recently. Theoretical and some experimental results have indicated that these monolayer TMD alloys exhibit direct-gap properties and remain stable at room temperature, making them attractive for optoelectronic applications. Here we systematically compared the two approaches of forming MoS2xSe2(1-x) monolayer alloys: selenization of MoS2 and sulfurization of MoSe2. The optical energy gap of as-grown CVD MoS2 can be continuously modulated from 1.86 eV (667 nm) to 1.57 eV (790 nm) controllable by the reaction temperature. Spectroscopic and microscopic evidences show that the Mo-S bonds can be replaced by the Mo-Se bonds in a random and homogeneous manner. By contrast, the replacement of Mo-Se by Mo-S does not randomly occur in the MoSe2 lattice, where the reaction preferentially occurs along the crystalline orientation of MoSe2 and thus the MoSe2/MoS2 biphases are easily observed in the alloys, which makes the optical band gap of these alloys distinctly different. Therefore, the selenization of metal disulfide is preferred and the proposed synthetic strategy opens up a simple route to control the atomic structure as well as optical properties of monolayer TMD alloys.